Antifouling Activity of Celastroids Isolated from Maytenus Species, Natural and Sustainable Alternatives for Marine Coatings - Pérez, Miriam Cristina (2014)
A group of celastroids, quinone-methide nortriterpenes isolated from Maytenus vitis-idaea and Maytenus spinosa were assayed for their antifouling activity. Toxicity assays were performed on Balanus amphitrite nauplii, and the most promising compounds were then incorporated in soluble-matrix antifouling paints, which were tested in the ocean. The results obtained after a 45 day-field trial of the paints indicated in all cases promising antifouling potencies. Although all compounds showed antifouling activity on a wide range of organisms, tingenone and celastrol were the most effective inhibitors of the settlement of fouling organisms. The effect of these substances on nauplii in laboratory tests was temporary instead of toxic, with a high recovery rate, which may avert a potentially adverse ecological damage on the benthic community. These results may provide a more environmentally friendly alternative for the control of biofouling, replacing toxic additives actually in use in marine paints.